Methodological Guide to Co-design Climate-smart Options with Family Farmers - Andrieu, Nadine; Howland, Fanny C.; Acosta-Alba, Ivonne; Le Coq, Jean-François; Osorio, Ana Milena; Chia, Eduardo (2018)
Climate-smart agriculture (CSA) seeks to improve productivity for the achievement of food security (pillar 1: Productivity), to develop a better ability to adapt (pillar 2: Adaptation), and to limit greenhouse gas emissions (pillar 3: Mitigation). Technical and organizational innovations are needed to find synergies among those three pillars. Innovation (its creation and its operation) is a social phenomenon. Many studies worldwide have shown that promoting a sustainable change and innovation within organizations has to be analyzed and implemented with stakeholders. Thus, the ability of local actors to tackle climate change and mitigate its effects will depend on their ability to innovate and mobilize material and non-material resources, to articulate links among national policies, not only between themselves, but also undertaking actions at the local level. To support stakeholders in the development of responses to this challenge, we propose the development of open innovation platforms, in which all local actors may participate. These platforms are virtual, physical, or physico-virtual spaces to learn, jointly conceive, and transform different situations; they are generated by individuals with different origins, different backgrounds and interests (Pali and Swaans, 2013).